2015
DOI: 10.1097/iae.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Peptic Ulcer Disease in Central Serous Chorioretinopathy Patients

Abstract: Peptic ulcer disease and higher monthly income are independent risk factors for CSR. Whereas, patients with CSR also had increased risk for peptic ulcer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
7
0
5
Order By: Relevance
“…In addition to associations between CSCR and the administration of corticosteroids via different routes, our results confirmed that several previously well-recognized comorbidities, such as hypertension, diabetes mellitus, hyperlipidemia, chronic renal disease, peptic ulcer, psychiatric disease, coronary artery disease, and allergic respiratory disease, are risk factors for CSCR ( Table 2). 43 However, only peptic ulcer and coronary artery disease remained significant risk factors after conditional logistic regression was conducted ( Table 3). This finding was consistent with the results of several previous studies reporting that patients with preexisting peptic ulcer or coronary heart disease had a higher incidence of CSCR.…”
Section: Topical Ophthalmic Corticosteroid Use and Cscrmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to associations between CSCR and the administration of corticosteroids via different routes, our results confirmed that several previously well-recognized comorbidities, such as hypertension, diabetes mellitus, hyperlipidemia, chronic renal disease, peptic ulcer, psychiatric disease, coronary artery disease, and allergic respiratory disease, are risk factors for CSCR ( Table 2). 43 However, only peptic ulcer and coronary artery disease remained significant risk factors after conditional logistic regression was conducted ( Table 3). This finding was consistent with the results of several previous studies reporting that patients with preexisting peptic ulcer or coronary heart disease had a higher incidence of CSCR.…”
Section: Topical Ophthalmic Corticosteroid Use and Cscrmentioning
confidence: 99%
“…This finding was consistent with the results of several previous studies reporting that patients with preexisting peptic ulcer or coronary heart disease had a higher incidence of CSCR. 43,44 Additionally, several reports have demonstrated that after antibiotic treatment for H. pylori infection, patients with both peptic ulcer and CSCR showed an improvement in CSCR. 26,45,46 This study had several strengths.…”
Section: Topical Ophthalmic Corticosteroid Use and Cscrmentioning
confidence: 99%
“…Keywords никаких данных о заболеваемости, а также исследований по изучению факторов риска развития центральной серозной хориоретинопатии в РФ. Результаты исследований в направлении оценки возможных факторов риска развития ЦСХП, проведенных в разных странах, также демонстрируют различные, часто противоречивые результаты [7][8][9][10][11][12][13][14][15]. Факторы и состояния, увеличивающие риск развития данного заболевания, условно можно разделить на химические, биологические, психосоматические и социально-демографические.…”
Section: Introductionunclassified
“…Химические факторы риска ЦСХП По результатам различных исследований в качестве химических факторов риска в возникновении заболевания выступают: использование стероидов [7][8][9][10][11][12][13][14], применение антибиотиков [7], табакокурение и употребление алкоголя [7,11], регулярное применение психофармакологических препаратов (нейролептиков или антидепрессантов) [8,16], применение антацидов или антирефлюксных медикаментов [9]. Изучались также такие возможные факторы, как использование нестероидных противовоспалительных средств [11,15], антигистаминных препаратов [7,9], амфетаминов [9], при этом связь с развитием ЦСХП в данных исследованиях не была продемонстрирована.…”
Section: Introductionunclassified
See 1 more Smart Citation